Report of the Twenty-seventh Regular Meeting of the Executive Committee - Executive Committee (EC) (2025)
The meeting is held to address informative working documents such as the Hemispheric Program on Agroenergy and Biofuels and the Hemispheric Program on Biotechnology and Biosafety. It also addresses the report of the CCEAG meeting and issues related to strengthening the support of IICA Member States for FONTAGRO and the institution's action in support of the development of organic agriculture.